Investing in agricultural water management to benefit smallholder farmers in Ethiopia. AgWater Solutions Project country synthesis report - Evans, Alexandra E.V.; Giordano, Meredith A.; Clayton, Terry (International Water Management Institute, 2012)
The AgWater Solutions Project, carried out between 2009 and 2012, focused on resolving water issues faced by smallholder farmers. The project examined existing Agricultural Water Management (AWM) solutions, together with factors that influence their adoption and scaling up. The project aimed to identify investment opportunities in AWM that have high potential to improve the incomes and food security of poor farmers. The work was undertaken in the African countries of Burkina Faso, Ethiopia, Ghana, Tanzania and Zambia, and in the Indian States of Madhya Pradesh and West Bengal. This Working Paper series summarizes results and recommendations from the research carried out in each of these countries and states.